A study on safety during building demolition work / Jasmani Muhamad Rejab - Muhamad Rejab, Jasmani (Faculty of Architecture, Planning and Surveying, 2010)
Nowadays, to achieving a develop status, shortage of land and space will requires existing structures to be demolished in order to make way for new development. The demolition work are create dangerous to all person involved in demolition works and safety measures should be considered. This research was conducted to study on safety precautions during building demolition work. The research was commenced by introduction to all theory which is related to demolition work such as definition of demolition, demolition method and etc. To more understanding about the types of safety precautions to taken during demolition work, the survey has been conducted of questionnaire has been distributed to the contractor and worker. The distributed questionnaire has been answered by various of the company management such as Project Manager, Health and Safety Officer, Supervisor, Site Engineer and Site Coordinator which to gather the various view on types of safety precautions during building demolition work. The interview session was carried out between Local Authority to find out the enforcement and roles of Local Authority during building demolition work. The questionnaire also distributed to public to find out their opinion about enforcement and roles of Local Authority. The all data collected from the survey has been analyzed and the finding was to achieve the objective in the dissertation. After the finding have recognized, some recommendation and suggestion for future research will make to improve the safety measures and reduce the risk in building demolition work.